PRODUCTION OF LIGHTWEIGHT CONCRETE USING OIL PALM SHELL (OPS) AGGREGATES - Teo , D.C.L.; Mannan , M.A.; Kurian, V.J. (ConMat 2009, 2009)
MalaysiaABSTRACT: It has been reported that OPS can be used as coarse aggregate substitute in concrete. Since OPS is an organic material, its properties differ from that of conventional granite aggregates. OPS is lightweight in nature and has bulk density of about 590 kg/m3. Consequently, the resulting concrete is lightweight. This paper presents some of the engineering properties of lightweight OPS concrete namely the compressive strength, split tensile strength, modulus of rupture and modulus of elasticity. Comparisons of the basic engineering properties of granite concrete (normal weight concrete) and OPS concrete (lightweight concrete) are also given. Results show that OPS aggregate can be used as an alternative to the conventional granite aggregates for the production of lightweight concrete. The utilisation of OPS as aggregate replacement in concrete is a good way of practicing sustainable development. Keywords: lightweight concrete, oil palm shell (OPS), solid waste, engineering properties, sustainable development